Inovasi Sistem Filtrasi dengan Substrat Filter Fisik dan Kimia untuk Budidaya Ikan Air Tawar di Kolam - Heru Kartika Candra; Rinova Firma Cahyani; Syamsudin Noor; Muhammad Bahit; Dwi Mulyani (Jurnal Pengabdian Masyarakat Waradin, 2025)
Water is one of the things that is important for life, it is even more important if the water that is obtained can provide other benefits. This is the case for freshwater fish breeders in the Kemuning tributary of the North Banjarbaru River, South Kalimantan. Water is an important variable because water is the medium where fish live. Freshwater fish of good quality are a superior commodity for fisheries cultivation in Indonesia in general. This aquatic organism is the same as freshwater fish in general which breathe using gills (operculum). The treatment of the freshwater fish cultivation process requires a flowing water media system with sufficient oxygen content. For this reason, several tools are needed to maintain the quality of pool water, namely a pool water filter (filter), a water suction and spray tool to regulate water circulation and an aerator to produce air bubbles. In this service activity, a water filter will be made with physical and chemical substrates to filter pond water with a water circulation system so that the filtered water has good water quality to support the life cycle of freshwater fish. As power to run the supporting equipment in the water filtering system, electricity is used by utilizing sunlight using solar cells. In this community service activity, to overcome existing problems, a pool water filter will be made with physical and chemical substrates. Making freshwater fish pond water filters using Bioring, Charcoal, Japmate, and Bio Foam substrates, where these 4 substrates provide good water quality results, namely, temperature 28.1–30.30C, pH7.4–8.1, DO 5.246 .53mg/L, NH 30.06–0.40mg/L, NO2 0.056–0.90mg/L and NO3-0.28–0.190 mg/L, the highest survival test (SR) in the bioring treatment was 86, 66%, the feed conversion ratio (FCR) test yielded a result of 3.10%. Meanwhile, the specific growth rate (SGR) test for freshwater fish was found to be 1.15%. However, of course, the more important target is to provide knowledge about good freshwater fish cultivation for residents of the Kemuning tributary, Loktabat Utara Banjarbaru Village, with an increase in knowledge of approximately 85% from before the PPM activities. The main output of this activity is an accredited Community Service Journal, in addition to water filtering equipment products with physical and chemical filter substrates.